Analisis Daya Saing Dan Faktor Yang Mempengaruhi Ekspor Teh Indonesia Di Delapan Negara Asean - Natasya Ali (Universitas Labuhanbatu, 2023)
Tea is one of the important commodities and potential for Indonesia. However, recently there are problems in the Indonesian tea industry, the volume of tea production, productivity, and export volume of Indonesian tea on average tend to decrease from year to year, but on the other hand the tea industry in several other ASEAN countries tend to increase. This study aims to see whether Indonesian tea has a comparative advantage in the domestic markets of eight Asian countries and what factors affect the export value of Indonesian tea. This analysis using RCA, RSCA and Gravity Modelusing panel data. The tea commodity Data used is tea with a 4-digit code 0902, with a time period of 2011-2020. It was found on average that Indonesian tea in the domestic market of eight countries joined in ASEAN has a comparative advantage. Furthermore, it was found in this study that the GDP of the export destination country, Indonesia'S GDP, economic distance, and Consumer Price Index have a significant influence on the value of Indonesian tea exports.. Indonesian GDP & CPI of destination countries have a significant positive relationship to the value of Indonesian tea exports. While the destination country'S GDP and economic distance have a significant negative relationship.